The concept of Evil and its semantic space by the Russian media - Mira Artyna, Urana Darzha, Rimma Bytotova, Lyubov Kara-ool, (Opción, 2019)
The article presents an analysis of the placement within the semantic space of the concept of evil belonging to various classes of autonomous words. Research materials are introduced into scientific circulation for the first time. The electronic versions of the newspaper Inform Plus were written out using the method of continuous sampling. As a result, it is revealed that the ways of verbalizing the signs of the figurative component of the concept of evil. The study reflects the changes that have occurred in the minds of modern people under the influence of socio-cultural realities in the language of the media.